Children making sense of economic insecurity: Facework, fairness and belonging. (March 2017) - Butler, Rose
This article contributes to our understanding of how children cope with economic insecurity in affluent nations. Based on research with children and adults in regional Australia, it argues for the importance of cultural narratives in making sense of children's strategies to cope with financial hardship. Drawing on Goffman's concept of 'facework', and recent analysis by Pugh, it analyses the complex forms of facework that children use to manage situations of economic insecurity and shows how such practices may be anchored in cultural narratives of 'fairness'. Goffman's 'facework' refers to the expressive order required to save face, a term used to signify how we participate in a social regime, particularly when we perform unexpected feelings. In this article, the author develops a theoretical framework to analyse three types of facework used by children from low-income families in this Australian context, and coins these practices 'going without', 'cutting down', and 'staying within'. Through such facework, children sought to maintain inclusion and uphold dignity, practices which were increasingly difficult amidst rising inequality. This raised contradictions in belonging and acceptance among others, particularly for children from refugee backgrounds.